ANALISIS KEBUTUHAN MATERI PEMBELAJARAN PADA MATAKULIAH "LE FRANí‡AIS DU TOURISME" - Pranowo, Dwiyanto Djoko; Sumiyati, Siti (Diksi, 2021)
(Title: Needs Analysis of Learning Language and Nonlanguage in Course Subject of Tourism). Educational programs are always designed to achieve a profile of outcome that is formulated based on the needs in accordance with the employment demands and scientific vision. This paper is about a research that aims to 1) identify students' French language competencies, 2) identify the need for tourism French language knowledge and skills, and 3) identify non-language knowledge needs that support students' competence in using French for tourism. This research was conducted at the FBS UNY campus. Data of this descriptive research was obtained by using the observation sheet for the data source from the video recordings. The research subjects are French Language Education students who have taken the Francais du Tourisme (FdT) course. The results showed that 1) students' communicative competence in French is on the B1 level, 2) The need for French language skills and tourism knowledge is an increase in communicative and linguistic competencies 3) The need for non-linguistic knowledge is about the history of Indonesia, the nation and state of Indonesia , as well as culture including customs.Keywords: need assessment, communicative competence, language competence, Franí§ais du Tourisme